Citrus Production on the Sandy Soils of Southwest Florida - R. M. Muchovej; Edward A. Hanlon; Thomas Obreza; Monica Ozores-Hampton; Fritz M. Roka; Sanjay Shukla; H. Yamataki; Kelly Morgan (EDIS)
SL-234, a 7-page illustrated fact sheet by R.M. Muchovej, E.A. Hanlon, T. Obreza, M. Ozores-Hampton, F.M. Roka, S. Shukla, H. Yamataki, and K. Morgan, reviews those challenges facing citrus growers dealing with soils, water management, and nutrients. The authors describe evolving strategies to efficiently produce citrus in southwest Florida on variable mineral soils. Published by the UF Department of Soil and Water Science, February 2006.